CHALLENGES AND PROSPECTS FACING THE DIGITIZATION OF HISTORICAL RECORDS FOR THEIR PRESERVATION WITHIN THE NATIONAL ARCHIVES OF ZIMBABWE PPT - Sigauke, Delight T.; Nengomasha, Dr C. T. (My University, 2012)
The National Archives of Zimbabwe Act (1986) has declared that historical records in particular must be protected against any destruction, defacing, alteration, mutilation or damage. Despite this, the pace at which digitization has been implemented by the National Archives of Zimbabwe and other memory institutions to ensure the protection and preservation of historical records and other valuable information materials, has been slack and ad-hoc. This paper will present and discuss the circumstances and challenges facing the country’s National Archiving institution in embarking on digitization efforts to preserve selected public and private historical records and archives-generated public registries, memory institutions and other information centres in Zimbabwe.
Keywords: Zimbabwe, National Archives of Zimbabwe, digitization, electronic records and archives, digital preservation 1